Isoprene and α-pinene deposition to grassland mesocosms - Spielmann, Felix M.; Langebner, Stephan; Ghirardo, Andrea; Hansel, Armin; Schnitzler, Jörg-Peter; Wohlfahrt, Georg (Plant and soil, 2017)
Background and aims Isoprene and monoterpenes account for approximately two thirds of the biogenic volatile organic compounds (BVOC) emitted annually by vegetation into the atmosphere. Previous research focussed on the magnitude of and controls on emissions of these two compounds by emitting plant species, while the role of soils and non-emitting plant species as potential sinks has been mostly ignored. The objective of the present study is to characterize the deposition of isoprene and α-pinene (a monoterpene) to non-emitting grassland plant mesocosms. Methods We conducted a laboratory experiment with mesocosms of two forb and one graminoid plant species. Plants and soils together and bare soils only were subject to increasing ambient isoprene and α-pinene concentrations (0-10 ppbv) and the corresponding BVOC exchange rates were quantified. Results Our major findings are that (i) soils were the dominant sink for the deposition of α-pinene and isoprene in grassland mesocosms, (ii) the presence of above-ground biomass of non-emitting plant species decreased the isoprene and α-pinene deposition in the majority of all cases, and (iii) the net deposition correlated inversely with the ambient concentrations. Conclusions Our results call for a more in-depth analysis of soil BVOC exchange to better estimate the contribution of soils to the ecosystem-atmosphere BVOC exchange.